ESTUDO DA PERMEABILIDADE DAS ÁREAS DAS JUNTAS DE PAVIMENTO INTERTRAVADO - Garcia, Emmanuelle S. H.; Lima, Geannina T. d. S.; Ghisleni, Geisiele; Pozzobon, Cristina E. (Salão do Conhecimento, 2013)
Resumo